2017
DOI: 10.1590/abd1806-4841.20175209
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic patterns of melanocytic nevi in children and adolescents: a cross-sectional study

Abstract: BackgroundChildhood is a dynamic period regarding nevogenesis. Dermoscopy is a noninvasive technique, recommended for the evaluation of pigmented cutaneous lesions.ObjectivesThe purpose of this study was to describe the structures and dermoscopic patterns of melanocytic nevi observed in children and adolescents.MethodsDermoscopy with photographic documentation was used for nevi located on the face, trunk, and extremities of 38 patients aged from one to 16 years examined at the Pediatric Dermatology Outpatient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Participants were examined clinically and with dermoscopy. Identification of naevi was based on the presence of the following dermoscopic features: pigmented network, globules, streaks, pseudopods, structureless, pinkish, and blue homogeneous colour . All study lesions were photographed using a dermoscope (Dermlite ® DL3; 3Gen, San Juan Capistrano, CA USA), attached to an adapter for a tablet device (iPad ® Mini 2; Apple, Cupertino, CA, USA), using polarized and nonpolarized mode.…”
Section: Reportmentioning
confidence: 76%
See 1 more Smart Citation
“…Participants were examined clinically and with dermoscopy. Identification of naevi was based on the presence of the following dermoscopic features: pigmented network, globules, streaks, pseudopods, structureless, pinkish, and blue homogeneous colour . All study lesions were photographed using a dermoscope (Dermlite ® DL3; 3Gen, San Juan Capistrano, CA USA), attached to an adapter for a tablet device (iPad ® Mini 2; Apple, Cupertino, CA, USA), using polarized and nonpolarized mode.…”
Section: Reportmentioning
confidence: 76%
“…Our patients were mostly young, so we compared our findings with a previous study evaluating the patterns of naevi in 38 Brazilian children and adolescents without OCA . That study found three main patterns of naevi: reticular (39%), homogeneous (23%) and globular (16%), which were similar to our series, although with different frequencies.…”
Section: Reportmentioning
confidence: 99%
“…Pediatric nevi can grow more rapidly or present other worrisome dermoscopic features, such as the halo phenomenon. 8,18 Dermoscopy as a standard diagnostic tool can allow assessment of the nevus architecture. Piazza et al 18 evaluated dermoscopic patterns of 38 melanocytic nevi in children.…”
Section: Discussionmentioning
confidence: 99%
“…8,18 Dermoscopy as a standard diagnostic tool can allow assessment of the nevus architecture. Piazza et al 18 evaluated dermoscopic patterns of 38 melanocytic nevi in children. Based on their limited cohort, the authors found a dominance of the globular pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that there were differences of dermoscopic features and patterns in different age stages, gender, body location of lesions ( 20 , 21 ). General information such as age, gender, anatomical locations were collected in this study.…”
Section: Methodsmentioning
confidence: 99%